Relationship between expression of p53 protein in breast cancer and axillary lymph node metastasis - Zhang Fang (Clinical Surgical Oncology)
Objective: To explore the expression of p53 protein in cancer tissue of breast cancer, analyze the relationship between positive rate of expression of p53 protein and axillary lymph node status. Method: 137 breast cancer patients in general hospital of PLA from June 2023 to October 2023 were selected and divided into axillary lymph node metastasis group and non-axillary lymph node metastasis group according to routine pathological outcome after surgery. Detect the situation of expression of p53 protein in cancer tissue using immunohistochemical method. The rate of expression of p53 protein between axillary lymph node metastasis group and non-axillary lymph node metastasis group were compared by χ2 test. At the same time, the relationship between the expression of p53 protein in breast cancer tissue and the age, the longest tumor diameter and tumor TNM stage was analyzed. Result: The rate of expression of p53 protein was 60.78%, 43.02% in the axillary lymph node metastasis group and non-axillary lymph node metastasis group respectively. The difference was statistically significant (χ2 ​= ​4.040, P ​= ​0.044＜0.05). The expression of p53 protein in breast cancer tissue was of no relationship with age (P ​= ​0.945＞0.05),the longest tumor diameter (P ​= ​0.200＞0.05) and tumor TNM stage (P ​= ​0.300 ​> ​0.05). Conclusion: There was a close relationship between expression of p53 protein in breast cancer tissue and axillary lymph node metastasis, and it can be regard as a predictive factor in the axillary lymph node status.